Direct Alignment and Patterning of Silver Nanowires by Electrohydrodynamic Jet Printing. Issue 19 (13th June 2014) - Lee, Hyungdong; Seong, Baekhoon; Kim, Jihoon; Jang, Yonghee; Byun, Doyoung
<x xml:space="preserve">Abstract</x> Highly aligned and patterned silver nanowires (Ag NWs) are investigated by using electrohydrodynamic (EHD) jet printing. Interaction between the flow field and the electric field as well as the mechanical stretching of the fiber jet can successfully align the Ag NWs inside the jet fiber. This technique can be applied in fabricating 1D nanostructures‐based printed micro/nanoscale devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>